Improving adherence and clinical outcomes in self-guided internet treatment for anxiety and depression: randomised controlled trial. - Nickolai Titov; Blake F Dear; Luke Johnston; Carolyn Lorian; Judy Zou; Bethany Wootton; Bethany Wootton; Jay Spence; Peter M McEvoy; Ronald M Rapee (PLoS ONE)
Background Depression and anxiety are common, disabling and chronic. Self-guided internet-delivered treatments are popular, but few people complete them. New strategies are required to realise their potential. Aims To evaluate the effect of automated emails on the effectiveness, safety, and acceptability of a new automated transdiagnostic self-guided internet-delivered treatment, the Wellbeing Course, for people with depression and anxiety. Method A randomised controlled trial was conducted through the website: www.ecentreclinic.org. Two hundred and fifty seven people with elevated symptoms were randomly allocated to the 8 week course either with or without automated emails, or to a waitlist control group. Primary outcome measures were the Patient Health Questionnaire 9-Item (PHQ-9) and the Generalized Anxiety Disorder 7-Item (GAD-7). Results Participants in the treatment groups had lower PHQ-9 and GAD-7 scores at post-treatment than controls. Automated emails increased rates of course completion (58% vs. 35%), and improved outcomes in a subsample with elevated symptoms. Conclusions The new self-guided course was beneficial, and automated emails facilitated outcomes. Further attention to strategies that facilitate adherence, learning, and safety will help realise the potential of self-guided interventions. Trial registration Australian and New Zealand Clinical Trials Registry ACTRN12610001058066.